Type of D-dimer assay determines the diagnostic yield of computed tomography in patients suspected for pulmonary embolism - Jorn L.J.C. Assmann; Adriaan J. van Gammeren; Reinier A. Sprenger; Saskia de Wit; Huib Ceelie; Frank W.G. Leebeek; Mark W.M. Schellings (Research and Practice in Thrombosis and Haemostasis, 2025)
Background: Pulmonary embolism (PE) is a life-threatening condition with high morbidity and mortality. The diagnosis of PE is challenging due to nonspecific symptoms, making reliable diagnostic tools essential. This study addresses the clinical impact of interassay variability in D-dimer measurements on the utilization and diagnostic yield of computed tomography pulmonary angiography (CTPA). Objectives: To investigate the effect of different D-dimer assays on the decision to perform CTPA and the subsequent diagnostic yield in patients with suspected PE. Methods: This retrospective, multicenter cohort study analyzed data from 3 teaching hospitals in the southwest region of the Netherlands, covering the years 2018, 2019, 2022, and 2023. The study included data from 40,096 clinically requested D-dimer results and 11,372 CTPA records of patients with suspected PE. The D-dimer assays used were the Roche Tina-quant and Siemens INNOVANCE. Results: The study found significant differences in CTPA utilization and diagnostic yield based on the D-dimer assay used. In 2018 to 2019, hospitals using the Roche Tina-quant assay ordered 21% fewer CTPA scans and had a 9% higher positivity rate compared with those using the Siemens INNOVANCE assay. Conclusion: The findings highlight the necessity for assay-specific cutoff values or, ideally, the standardization of the D-dimer assay to optimize the accuracy and efficiency of PE diagnosis. This study demonstrates that the choice of D-dimer assay significantly influences the clinical management of suspected PE, affecting both the number of CTPA scans performed and the positivity rate of these scans. Implementing assay-specific cutoff values or standardization of the D-dimer assay could reduce unnecessary CTPA scans, minimize patient exposure to radiation, and lower healthcare costs. These results advocate enhanced collaboration between clinicians and laboratory specialists to accurately interpret D-dimer results within the context of the specific assay used. Future research should validate these findings in prospective studies and explore standardized protocols that account for interassay variability.